2022
DOI: 10.1007/s10067-022-06286-w
|View full text |Cite
|
Sign up to set email alerts
|

The enigma of mixed connective tissue disease—challenges in routine care

Abstract: Objectives As a rare and heterogeneous disease, mixed connective tissue disease (MCTD) represents a challenge. Herein, we aimed to unravel potential pitfalls including correct referral diagnosis, distinction from other connective tissue diseases (CTD) and treatment modalities. Methods We characterised the MCTD cohort at our tertiary referral centre. All patients were evaluated for fulfilment of classification criteria of various CTDs. SLEDAI-2 K and EUSTAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…The Alarcon-Segovia criteria are often used to aid in the diagnosis of MCTD, but there is currently no tool to measure disease activity [ 1 , 5 ]. As MCTD is a heterogeneous disease with nonspecific symptoms, it is estimated that only 10-33% of patients will fulfill the Alarcon-Segovia criteria at the time their first symptom appears [ 1 , 2 ]. In fact, many patients will only have one predominant symptom for up to 10 years prior to diagnosis, and 90% of patients are diagnosed with other conditions first [ 1 , 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Alarcon-Segovia criteria are often used to aid in the diagnosis of MCTD, but there is currently no tool to measure disease activity [ 1 , 5 ]. As MCTD is a heterogeneous disease with nonspecific symptoms, it is estimated that only 10-33% of patients will fulfill the Alarcon-Segovia criteria at the time their first symptom appears [ 1 , 2 ]. In fact, many patients will only have one predominant symptom for up to 10 years prior to diagnosis, and 90% of patients are diagnosed with other conditions first [ 1 , 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…As MCTD is a heterogeneous disease with nonspecific symptoms, it is estimated that only 10-33% of patients will fulfill the Alarcon-Segovia criteria at the time their first symptom appears [ 1 , 2 ]. In fact, many patients will only have one predominant symptom for up to 10 years prior to diagnosis, and 90% of patients are diagnosed with other conditions first [ 1 , 2 , 4 ]. Prior studies have shown that Raynaud’s phenomenon is the most common presenting symptom, but symmetric arthralgias are the most predominant symptom by the time patients fulfill the Alarcon-Segovia criteria [ 1 , 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations